2003
DOI: 10.1002/jgt.10137
|View full text |Cite
|
Sign up to set email alerts
|

A list analogue of equitable coloring

Abstract: Given lists of available colors assigned to the vertices of a graph G, a list coloring is a proper coloring of G such that the color on each vertex is chosen from its list. If the lists all have size k, then a list coloring is equitable if each color appears on at most dn(G )/ke vertices. A graph is equitably k-choosable if such a coloring exists whenever the lists all have size k. We prove that G is equitably k-choosable when k ! maxfÁ(G ),n(G )/ ------------------ Kostochka and West

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 10 publications
1
71
0
Order By: Relevance
“…A list analogue of equitable coloring was introduced by Kostochka, Pelsmajer and West [53]. A list assignment L for a graph G assigns to each vertex v ∈ V (G) a set L(v) of allowable colors.…”
Section: Equitable List Coloringmentioning
confidence: 99%
See 1 more Smart Citation
“…A list analogue of equitable coloring was introduced by Kostochka, Pelsmajer and West [53]. A list assignment L for a graph G assigns to each vertex v ∈ V (G) a set L(v) of allowable colors.…”
Section: Equitable List Coloringmentioning
confidence: 99%
“…Nevertheless, Kostochka, Pelsmajer and West [53] suggested that the following analogue of the Hajnal-Szemerédi Theorem holds.…”
Section: Equitable List Coloringmentioning
confidence: 99%
“…In [17], a list analogue of equitable coloring was considered. A list assignment L for a graph G assigns to each vertex v ∈ V (G) a set L(v) of allowable colors.…”
Section: Equitable Partitions Of D-degenerate Graphsmentioning
confidence: 99%
“…Lih's paper [14] surveys some basic results on equitable colorings and how the bound of ∆ + 1 can be replaced by ∆ for certain classes of graphs. Applications of the Hajnal-Szemerédi theorem and recent results on equitable colorings of graphs can be found in (among others) [1], [2], [9], [11], [12], [19]. Equitable coloring turned out to be useful in establishing bounds on tails of sums of dependent variables [6], [8], [18].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%